Peramalan Data Penduduk Miskin Provinsi Nusa Tenggara Barat (NTB) Model Auto Regressive Integrated Moving Average (ARIMA) - Mizan, Samsul; Pelangi R, Baiq Dewi; Suriani, Novia; Muhaimin, Rizal; Laili, Nihajatul; Ernita, Weni (JP3M: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN MATEMATIKA, 2019)
This study aims to predict the number of poor people in West Nusa Tenggara (NTB) in 2019. Data used as many as 17 years and processed with a computer program Eviews to see the pattern and results in the auto regressive integrated moving average (ARIMA) model. This modeling phase starts from testing data stationarity, model identification, model estimation, model verification, and forecasting. Based on the results of this study, the prediction of the number of poor people in 2019 was 684,158 people. with MAD error parameters of 30.507,5625, MSE of 1.989.563.779, and MAPE of 3%.